The Effectiveness of Blooket Learning Media in Improving Reading Comprehension of Personal Letters among Grade XI Students of SMA PGRI Pekanbaru (Lembaga Pengembangan Kinerja Dosen, 2025)
Reading comprehension, especially in personal letter texts, is challenging for many Indonesian high school students due to limited vocabulary and low motivation. Blooket, a game-based learning platform, offers potential to improve engagement and learning outcomes.Objective: This research aims to examine the effectiveness of Blooket learning media in improving students’ reading comprehension of personal letters at Grade XI of SMA PGRI Pekanbaru. A quantitative approach with a quasi-experimental non-equivalent control group design was used. The sample consisted of 39 students, divided into an experimental group taught with Blooket and a control group taught conventionally. Pre-tests and post-tests (25 multiple-choice items) were administered, and data were analyzed using normality, homogeneity, The experimental group’s mean score increased from 55.21 to 84.96, while the control group improved from 51.53 to 72.00. The paired sample t-test yielded p = 0.000 (<0.05), indicating a significant effect of Blooket on reading comprehension. Blooket’s interactive and competitive features effectively enhanced students’ reading comprehension of personal letters, motivation, and participation, making it a valuable alternative for teaching short functional texts in EFL classrooms.